Synergistic Effect of Fragrant Herbs in Japanese Scent Sachets - Fujiwara, Yumi; Ito, Michiho (Planta Medica, 2015)
The sedative activity of eight aromatic natural medicines that are traditionally used in Japanese scent sachets was examined using an open field test with mice. Galangal (Kaempferia galanga), patchouli (Pogostemon cablin), sandalwood (Santalum album), spikenard (Nardostachys chinensis), cinnamon (Cinnamomum cassia), clove (Syzygium aromaticum), star anise (Illicium verum), and borneol (Dryobalanops aromatica) distilled oils were used. These natural medicines have various pharmacological effects. For example, galangal has insecticidal activity and clove extracts possess strong total antioxidant activity. Aromatherapy, a well-known complementary medicine system that uses inhalation, has recently attracted much attention. The sedative activity of inhaled aromatic compounds or essential oils has been examined by measuring the spontaneous motor activity of mice in an open field test. The galangal, patchouli, sandalwood, spikenard, and borneol oils showed significant sedative effects. The effect was stronger for a mixture of the five oils than for any of the single oils. This suggests that the oil mixture may have synergistic activity. Sedative activity was not observed when inactive oils (cinnamon, clove, and star anise) were added to the mixture of the five active oils.
Keywords: sedative effect; inhalation; fragrant herbs; synergistic effect